2004 43rd IEEE Conference on Decision and Control (CDC) (IEEE Cat. No.04CH37601) 2004
DOI: 10.1109/cdc.2004.1429377
|View full text |Cite
|
Sign up to set email alerts
|

Stability of continuous-time distributed consensus algorithms

Abstract: We study the stability properties of linear time-varying systems in continuous time whose system matrix is Metzler with zero row sums. This class of systems arises naturally in the context of distributed decision problems, coordination and rendezvous tasks and synchronization problems. The equilibrium set contains all states with identical state components. We present sufficient conditions guaranteeing uniform exponential stability of this equilibrium set, implying that all state components converge to a commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
500
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 583 publications
(512 citation statements)
references
References 30 publications
11
500
0
1
Order By: Relevance
“…The following preliminary result of [93] will be needed in Section 7.2. First, for any δ > 0 and any matrix B, the δ-digraph is defined as the digraph where edge (i, j) exists if B ij ≥ δ.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…The following preliminary result of [93] will be needed in Section 7.2. First, for any δ > 0 and any matrix B, the δ-digraph is defined as the digraph where edge (i, j) exists if B ij ≥ δ.…”
Section: Preliminary Resultsmentioning
confidence: 99%
“…Therefore, from Theorem 1 in [14], we conclude that the variables ω a k , b a k and c a k asymptotically converge to the consensus valuesω,b andc respectively.…”
Section: Stabilization Of Relative Equilibria In the Presence Of Lmentioning
confidence: 69%
“…Since s j = s av , and x j is parallel to ω for every j ∈ G 2 , we conclude from (23) that this set does not correspond to global minima of (14). It can be shown that under suitable perturbations of x k , k ∈ G 2 (such that s av is constant) (23) is decreasing and therefore conditions (22) define an unstable set (the details are omitted due to space constraints).…”
Section: A Stabilization About An Axis Of Rotation With a Fixed Dirementioning
confidence: 94%
“…Flocking dynamics described by Reynolds' rule are known to be asymptotically stable under fairly weak conditions on the topology of the underlying graph [17], [18], [24], [25]. Stronger results, such as exponential stability, have been found for linear time-varying consensus protocol for single integrator systems [26], in the context of synchronization for second-order Euler-Lagrange systems [20]- [22], and using tools from dynamical systems theory for time-invariant, undirected graph topologies in second-order, two-dimensional (2-D) flocking dynamics [27]. Preliminary results on exponential stability of flocks under tree and star topology constraints are presented in [8].…”
Section: A Overview Of the Literaturementioning
confidence: 90%